Amyand’s hernia with healthy looking vermiform appendix, treatment of three cases with review of literatures - Naiem, Nabil I. (Journal of the Faculty of Medicine Baghdad, 2018)
The term Amyand’s hernia refers to an incarcerated inguinal hernia containing the vermiform appendix, which may be completely healthy, inflamed or perforated. (1) In almost 1% of all inguinal hernias Amyand’s hernia is detected and acute appendicitis in Amyand’s hernia cases accounts only for 0.1% “ 0.07-0.13”. (5)Amyand’s hernia is named after Claudius Amyand, who on December, 6,1735 performed the 1st successful appendectomy during the treatment of 11 years old boy presented with right inguinal hernia . During the surgery Amyand found a pin within the appendix which was encrusted with stone the appendix was found within the inguinal hernia sac. (2) It should not be confused with the incidental findings of cecal appendix within the femoral hernia sac “ de Garengeot’s hernia” which is first described by Rene de Garengeot in 1731(3.4) The reported mortality rate of Amyand’s hernia ranges from 5.5%- 30%. This variation occurs due to the effect of early diagnosis, giving proper treatment, preventing intra abdominal sepsis, and good postoperative care. (6) It is generally accepted that surgical treatment of Amyand’s hernia includes both appendectomy and hernia repair. (5,6.7) However, appendectomy in the absence of an inflamed appendix and the use of mesh in cases of appendectomy remain to be controversial. Some authors offer not to perform prophylactic appendectomy when non inflamed appendix is incidentally found in the hernial sac. (6) Others believe that appendectomy should be performed in all cases to prevent future reherniation and appendicitis. (8.9) It has been thought that it is impossible to reach sufficient number of Amyand’s hernias cases to get evidence- based data due to its rarity. Therefore it is logical to revise the classification and surgical treatment of Amyand’s hernia based on the case reports from different institutions. The aim of this study is to review the experience of mesh inguinal hernia repair without performing appendectomy in patients with Amyand’s hernia with healthy looking vermiform appendix with close postoperative follow up to detect recurrence or other postoperative complications.